Three new species of Chordodes and new data on hairworms (Nematomorpha) from Ecuador - de Villalobos, Cristina; Zanca, Fernanda; Yanez, Alvaro Barragan (Zootaxa, 2009)
The presently known freshwater Nematomorpha from Ecuador include only three species. Seven species of hairworms are herein firstly recorded from this country, which makes 10 the known species inhabiting Ecuador. Four of them are redescribed and three new species of Chordodes (C. alticuspis, C. ecuatoriensis and C. ruginosus) are described. All species are described using scanning electron microscopy. A list of all species known from Ecuador is also included.